INCIDENCE OF INTESTINAL PARASITES IN CHILDREN WITH CHRONIC SPONTANEOUS URTICARIA - BUKHARI , AA; BUKHARI , AA; AKRAM , A; NAEEM , N; ZAFAR , AF; ARSHAD , G (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to investigate the incidence of intestinal parasites in children who have been diagnosed with chronic spontaneous urticaria. A prospective control study was conducted at the Pathology Department of MMDC, Multan. The study included a total of 150 children, both from government and private schools. The children were divided into two groups: group A comprised 80 children diagnosed with chronic spontaneous urticaria, and group B included 70 healthy children. Group A was assessed for intestinal infections, and those with parasites were given anti-parasitic therapy. The outcomes were then evaluated. Out of the participants in group A, 18 (22.5%) had intestinal parasitic infections (IPI), compared to 10 (14.2%) in group B. Although the incidence of IPI was higher in group A, the difference was not statistically significant (P=.181). Blastocystis sp. was found in 14 (17.5%) patients in group A and 10 (14.2%) in group B. The eosinophil percentage in group A was 2% (.6% - 3.7%), and in group B was 1.5% (.6% - 2.2%) (P= .045). The total IgE value in group A was 97.6 IU/mL (ranging from 29-246 IU/mL), and in group B was 31.6 IU/mL (ranging from 14.2-65.8 IU/mL) (P <.001). Patients diagnosed with IPI were treated with metronidazole; out of the 18 patients, 10 (55.5%) saw an end to their urticaria symptoms. The results of this study suggest that Blastocystis sp. and D. fragilis were the most common parasites found in children with urticaria, which can disrupt their lifestyle.